Effectiveness of Jigsaw Cooperative Learning Model on Communication Skills of Elementary School Students: SLR - Putri, Anandha Noviyanti; Utama, Candra (Proceedings Series of Educational Studies, 2024)
This study examines the effectiveness of jigsaw type cooperative learning model in improving communication skills of elementary school students. This study aims to describe the effect of jigsaw type cooperative learning model on communication skills based on systematic literature review. The research method used is Systematic Literature Review with secondary data sourced from various literature studies. The research stages include data collection, data analysis, and conclusion drawing. The results showed that out of 7 relevant journal articles, the jigsaw model can effectively improve the communication skills of elementary school students. The conclusion of this study is that the Jigsaw Type Cooperative Learning Model shows significant effectiveness in improving the communication skills of elementary school students.